Applications of Multi-Channel Safety Authentication Protocols in Wireless Networks. - Chen, Young-Long; Liau, Ren-Hau; Chang, Liang-Yu (Journal of Medical Systems, 2016)
People can use their web browser or mobile devices to access web services and applications which are built into these servers. Users have to input their identity and password to login the server. The identity and password may be appropriated by hackers when the network environment is not safe. The multiple secure authentication protocol can improve the security of the network environment. Mobile devices can be used to pass the authentication messages through Wi-Fi or 3G networks to serve as a second communication channel. The content of the message number is not considered in a multiple secure authentication protocol. The more excessive transmission of messages would be easier to collect and decode by hackers. In this paper, we propose two schemes which allow the server to validate the user and reduce the number of messages using the XOR operation. Our schemes can improve the security of the authentication protocol. The experimental results show that our proposed authentication protocols are more secure and effective. In regard to applications of second authentication communication channels for a smart access control system, identity identification and E-wallet, our proposed authentication protocols can ensure the safety of person and property, and achieve more effective security management mechanisms.